The Theoretical Description for Sulfite and Nitrite Anodic Detection and Removal from Wine over Poly(9- Triphenylphosphazo)Acridine-Modified Electrode. - Lyudmyla V. Romaniv (Letters in Applied NanoBioScience. Volume 13, Issue 2, 2024, 7 Р, 2024)
A novel electroanalytical process for nitrite and sulfite anodic electrochemical determination in wine, based on the 9-triphenylphosphazoacridine conducting polymer as an anode modifier, has been investigated. 9-triphenylphosphazoacridine monomer may be obtained from 9-chloroacridine via 9 azidoacridine by reacting it with triphenylphosphine in ether. As for the sulfite and nitrite electrooxidation to sulfate and nitrate correspondently, it is given in conducting polymer matrix by two doping types. The analysis of the model has confirmed the efficiency of poly(9 triphenylphosphazo)acridine as an electrode modifier for sulfite and nitrite determination in wine, although the oscillatory behavior is relatively probable.
Keywords: nitrite; sulfite; electrochemical sensor, acridine derivative; conducting polymer; electrochemical oscillations; stable steady-state